2011
DOI: 10.1038/ajg.2011.302
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Early-Onset and Late-Onset Hepatocellular Carcinoma in Asian Immigrants With Hepatitis B in the United States

Abstract: HCC occurs in Asian immigrant HBV patients younger than currently recommended screening guidelines. A large majority of these early-onset patients did not have cirrhosis at the time of their HCC diagnosis; therefore, factors other than cirrhosis need to be considered when evaluating HCC risk in young patients. Factors associated with HCC development across all ages include cirrhosis and male gender, while family history and smoking history may identify younger Asian immigrant HBV patients at risk for HCC. Pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 28 publications
4
46
0
Order By: Relevance
“…Factors such as alcohol intake, genetic predisposition and aflatoxin may also affect risks differences between groups. Fujianese immigrants appear more likely to develop HCC at an early age (56) for reasons that are still unclear, but are likely related to some of those factors. Risk stratification using a comprehensive scoring system that accounts for age, gender, HBV VL, HBeAg status, and family history of HCC and genotype (18) may potentially provide a better way to calculate disease burden in specific subgroups and more effectively target individuals at a greater risk for HCC and for whom treatments may bring the greatest benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as alcohol intake, genetic predisposition and aflatoxin may also affect risks differences between groups. Fujianese immigrants appear more likely to develop HCC at an early age (56) for reasons that are still unclear, but are likely related to some of those factors. Risk stratification using a comprehensive scoring system that accounts for age, gender, HBV VL, HBeAg status, and family history of HCC and genotype (18) may potentially provide a better way to calculate disease burden in specific subgroups and more effectively target individuals at a greater risk for HCC and for whom treatments may bring the greatest benefit.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mortality from HCC is also higher in immigrant cohorts than their native-born counterparts [54,59]. Among immigrants with HBV, the onset of HCC tends to occur at a younger age than in the baseline population, and especially so among patients with a family history of HCC [60].…”
Section: Burden Of Chronic Liver Disease Among Migrantsmentioning
confidence: 99%
“…There was little difference between the 2 tumor-size groups and the liver function tests, but AFP mean values were much higher for the larger-tumor group (p < 0.0008). Platelets were also significantly different between the 2 groups (p < 0.0001) with only the small-tumor patients having thrombocytopenia, which has a much-cited association with HCC [12,13,14]. However, the means for the platelet counts in the larger-tumor group in our dataset were within the normal range.…”
Section: Resultsmentioning
confidence: 44%
“…An increase in the incidence of PVT with increased HCC size has been noted previously [23] and was a trend in our patients, as was elevated AFP levels and tumor size. We found that thrombocytopenia, which has previously been noted in association with cirrhosis and HCC [12,13,14,29,30], was significantly different between the 2 tumor-size groups and was unexpectedly more pronounced in patients with smaller tumors than in those with the larger ones.…”
Section: Discussionmentioning
confidence: 55%